Rethinking the future of Europe : a challenge of governance - Schepers, Stefan; Kakabadse, Andrew; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
Rethinking the Future of Europe has brought together three contrasting collections of contributions: the incrementalist perspective concerning the step by step development of Europe, the more radical reform/restructuring approach to the future of Europe, and a view of Europe from the outside.
Keywords: Science